Hastings Alumni Association-Fresno Chapter Luncheon Honoring Justice Donald Franson, Sr. - Watkins, Howard::::::::: (1988)
Justice Donald Franson, Sr. and Judge Annette LaRue standing; Law school Dean Mary Kay Kane seated Luncheon held at the Downtown Club